Development of story calendar media: Literacy resources for learning of narrative writing skills and character responsibilities - Rokhmani, Tri Astuti; Suhardi, Suhardi (Jurnal Prima Edukasia, 2021)
This research is motivated by the need for instructional media to improve narrative writing skills and the character of student responsibility. Because of this, a story calendar with the theme of responsibility was developed. This research is RnD research. Starting from research and information collecting, planning, develop a preliminary form of product, preliminary field testing, main product revision, main field testing, operational product revision. Based on the results of the media development that has been performed above, it can be concluded that the story calendar media are ready for implementation. The validity is proven by the validators, consisting of the media expert, material expert, language expert, and also from the teachers and students responses. The mean score from the expert and teachers responses belongs to the "Very Eligible" criteria. All the students' responses showed that they said "Yes" almost 100% in all the statements from the students' questionnaire. It is expected that the story calendar media can serve as an alternative to literacy media and supplementation learning material, especially for writing skills learning and developing student's responsibility character.